PMO-165 Potential impact of protease inhibitors in the South West Peninsula hepatitis C population. (28th May 2012) - Saunders, M; Sieberhagen, C; Taylor, L; Fry, F; McKenna, M; Needs, S; Chimakurthi, R; Cramp, M
Abstract : Introduction: Treatment of hepatitis C virus (HCV) with pegylated interferon and ribavirin achieves a sustained viral response (SVR) in 40%–50% of genotype 1 patients. 1 Protease inhibitors (PIs) increase SVR rates in treatment naïve genotype 1 patients to 63%–75%, but it is in those who failed to achieve an SVR with previous treatment that the most significant differences have been observed, particularly in those who relapse. 1 This study assessed the potential beneficial impact of PIs in a real world population undergoing HCV treatment in the South West Peninsula, identifying the number of eligible patients and considering population-specific issues to treatment. Methods: All patients treated for HCV in the South West Peninsula between January 2008 and December 2010 were identified by HCV nurse specialists. Proformas identifying treatment centre, patient characteristics, viral response, treatment compliance and outcome were completed and entered into a database for further analysis. Viral data from genotype 1 HCV patients identified those who relapsed, had viral breakthrough or were non-responders. Non-responders were further categorised into partial and null responders. Results: 361 patients from five centres (Plymouth, Exeter, Truro, Torbay and Barnstaple) were identified. 164/361 patients (45.4%) had genotype 1, of which 11.6% (n=19) were cirrhotic. 40.8% (n=67) achieved SVR, 15.9% (n=26) relapsed and 4.3% (n=7) had viral breakthrough. Of 33 (20.1%) non-responders, 20 were null responders, 11 partial responders and 2 had insufficient viral load data. 9.1% (n=15) stopped treatment early, 7.9% (n=13) were lost to follow-up and 1.8% (n=3) had no post-treatment viral load data available. 17 genotype 1 patients were treated in prison, of which, 11.7% (n=2) stopped treatment early and 41.1% (n=7) were lost to follow-up. Of the 97 (59.2%) genotype 1 cases who did not achieve SVR, at least 44/164 (26.8%) would have a very clear benefit from re-treatment with PIs. Conclusion: A significant number (26.8%) of genotype 1 treatment-experienced patients treated in the South West would benefit from re-treatment, with addition of a PI to their HCV treatment. Adherence with treatment and reliable follow-up of patients are crucial for safe treatment with PIs. Despite the provision of a good HCV service, a significant number of cases did not attend for prearranged reviews. At present, 7.9% of cases treated were lost to follow-up, with prisoners disproportionately unlikely to attend planned clinics. Competing interests: M Saunders: None declared, C Sieberhagen: None declared, L Taylor: None declared, F Fry: None declared, M McKenna: None declared, S Needs: None declared, R Chimakurthi: None declared, M Cramp grant/research support from: Unrestricted educational grants from Roche, MSD and Janssen, Conflict with: Served on advisory boards for Janssen, Roche, MSD and Gilead. Reference: 1. Ghany M, et al. An Update on Treatment of Genotype 1 Chronic Hepatitis C Virus Infection: 2011 Practice Guideline by the American Association for the Study of Liver Diseases. Hepatology 2011;54 :1433–44.